Predictive Value of Postoperative Peripheral CD4+ T Cells Percentage in Stage I–III Colorectal Cancer: A Retrospective Multicenter Cohort Study of 1028 Subjects - Li, Zhenhui; Li, Shaoyou; Liang, Yun; Pu, Hongjiang; Tu, Changling; Wu, Zhenyu; You, Dingyun (Cancer management and research, 2020)
Association of postoperative peripheral CD4+ T cells percentage and recurrence in colorectal cancer (CRC) remains to be explored. Therefore, we aimed to investigate the association between the postoperative peripheral CD4+ T cells percentage and recurrence in CRC patients. Consecutive stage I-III CRC patients without neoadjuvant treatment undergoing curative resection from January 2010 to July 2016 were identified in two Chinese centers. The association between the postoperative CD4+ T cells percentage, measured within 12 weeks after surgery, and recurrence-free survival (RFS) was analyzed. A total of 1028 patients were identified (training set: 913 patients, validation set: 115 patients). In the training set, the 5-year RFS rate of the 441 patients with abnormal postoperative CD4+ T cells percentage was significantly lower than that of those with normal percentage (70.3% [95% CI 65.7-75.2%] vs 77.6% [95% CI 73.7-81.7%] and unadjusted hazard ratio [HR] 1.36 [95% CI 1.04-1.78], 0.02). The result was confirmed in the validation set. Multivariable Cox regression analysis demonstrated that the association of postoperative CD4+ T cells percentage with 5-year RFS was independent both in the training and validation sets. In propensity score matching analysis, patients with normal postoperative CD4+ T cells percentage were found to have a favourable response to adjuvant chemotherapy (HR 0.29 [95% CI 0.12-0.72], =0.008). Postoperative peripheral CD4+ T cells percentage is a predictive biomarker for RFS in patients with CRC, which can identify those who will benefit from adjuvant chemotherapy.